Performance of Poplar (Populus deltoides Bartr. Ex Marsh.) Clones under Tarai Conditions of Uttar Pradesh - Misra, K. K.; Rai, P. N.; Jaiswal, H. R. (Indian Forester, 1995)
The performance of six year old 12 clones of poplar (Populus deltoides Bartr. ex Marsh.) were studied in intercropping system of management under Tarai conditions of Uttar Pradesh. Clone 6/64 performed better than other clones after six years of planting.